Texas Literary Outlaws : Six Writers in the Sixties and Beyond - Davis, Steven L., 1963- (Book collections on Project MUSE., 2004)
Davis makes extensive use of untapped literary archives to weave a fascinating portrait of six Texas writers, calling themselves the Mad Dogs, who came of age during a period of rapid social change: Bud Shrake, Larry L. King, Billy Lee Brammer, Gary Cartwright, Dan Jenkins, and Peter Gent.